2020
DOI: 10.1302/1863-2548.14.200090
|View full text |Cite
|
Sign up to set email alerts
|

The use of virtual reality in reducing anxiety during cast removal: A randomized controlled trial

Abstract: Purpose While virtual reality (VR) has been shown to be an effective distractor in children across a range of procedures, no studies have looked at its use within paediatric orthopaedics. The purpose of this study was to look at the use of VR in reducing anxiety levels in children during cast removal. In addition, the study aimed to find ways to enhance the efficiency of future VR trials in paediatrics. Methods A non-blinded randomized control trial took place in children aged four to 18 years. Intraprocedural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 20 publications
4
24
0
Order By: Relevance
“…Nevertheless, Hoxhallari et al reported a decrease in patient anxiety in upper limb surgery under local anesthesia in a prospective comparative study [17]. For pediatrics surgery, Jivraj et al showed a decrease in children anxiety with VR during cast removal [18]. Therefore, this study brings new arguments supporting VR interest in TKA.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Nevertheless, Hoxhallari et al reported a decrease in patient anxiety in upper limb surgery under local anesthesia in a prospective comparative study [17]. For pediatrics surgery, Jivraj et al showed a decrease in children anxiety with VR during cast removal [18]. Therefore, this study brings new arguments supporting VR interest in TKA.…”
Section: Discussionmentioning
confidence: 69%
“…In the present study, the mean age was 73.5 years old, with a slightly older population in group 1. The literature on VR experience mostly reflects the pediatric population [18,20,21]. In the study by Huang et al, the average age in VR group was 65 years [9].…”
Section: Discussionmentioning
confidence: 99%
“…In light of its peculiar features, virtual reality (VR) has proven to be a powerful tool to achieve this goal and, in fact, its use in this area is increasing [36,37]. VR also provides a control environment that submerges the user in a controlled but relaxed structure, making it possible to carry out screening tests and decreasing emotional distress [38]. The second group aims at selecting the best tests among the available ones [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this, psychometric tests will be delivered by relying on VR. Its characteristics, indeed, allow recreating an interactive environment with high fidelity, thus presenting any material in a playful and appealing way, which is likely to improve engagement and attention [38]. In addition, tests performing time will be reduced and the obtained results will be collected and stored more easily and in a convenient way for their use in the AI module.…”
mentioning
confidence: 99%
“…The educational structures tend to include ICTs with a higher compliance capacity, accessibility, and end-user attractiveness. Additionally, the utilization of virtual realities via mobile devices and headsets is increasing, as they allow the immersion and acquiring of theoretical or practical skills [15][16][17].…”
Section: Introductionmentioning
confidence: 99%